Quality in Qualitative Research – Can Qualitative Research Be Valid and Reliable? - Muszyński, Marcin (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
Every research project should ensure high quality. This is achieved through criteriathat are useful for evaluating a study. This chapter provides a synthetic review ofvarious perspectives on the criteria for assessing qualitative research, which can serve asguidelines for future scientific projects. Some of these criteria stem from the post-positivisttradition and were developed by mirroring quantitative criteria. On the other hand, someare rooted in the constructivist tradition. The text highlights the importance of selectingappropriate quality criteria.